Legitimation by constitution : a dialogue on political liberalism - Ferrara, Alessandro, 1953-; Michelman, Frank I., 1936- (Oxford : Oxford University Press, 2021)
'Legitimation by constitution' is a phrase coined by Michelman and Ferrara to represent an idea in Rawlsian political liberalism of reliance on a dualist democracy: ground-level laws are subject to the constraints of a legal constitution that all citizens, across the political spectrum, can accept as a framework for their collective politics.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Liberalism; Democracy